PRE-SOWING SEED TREATMENTS WITH SILICON NANO-IRON AND NANO-SILICON PARTICLES ON GERMINATION OF DRAGONHEAD - Sabaghnia, Naser; Yousefzadeh, Saeed; Janmohammadi, Mohsen; Mohebodini, Mehdi (Plant Breeding and Seed Science, 2016)
Nanotechnology is an emerging field of science widely exploited in agriculture in recent years. In this investigation, application of nanotechnology in agriculture via application of some nano-particles (nano-iron and nano-silicon) have been investigated in seed priming of dragonhead. Seeds were subjected to prehydration treatments by factor nano-silicon dioxide as; (S1) 0 mM or distilled water, (S2) 1 mM concentration and (S3) 2 mM concentration and and factor nano-iron oxide as; (F1) 0 Mm or distilled water, (F2) 1 mM concentration and (F3) 2 mM concentration. Germination percent, root fresh weight, shoot fresh weight, root length, shoot length, dry weight of the seed residue, root dry weight and shoot dry weight were measured. Analysis of variance showed significant variation for the main effect of nano-silicon dioxide as well as nanoiron dioxide in root length and dry weight of the seed residue. The interaction effect of nano-silicon × nanoiron priming treatments were significant in all of the measured traits except germination percentage and root fresh weight. The highest germination percentage was recorded in S2-F3, S3-F1 and S3-F3 while the root fresh weight was high in S2-F3 and treatments S1-F1 following to S2-F3 and S3-F2 produced the highest shoot fresh weight. Also, S2-F3 has the highest root length (16.1 cm) and the highest shoot length (18.4 cm). The best treatment combination suitable for obtaining of high values of germination characteristics of dragonhead was identified as S2-F3 (1 mM nano-silicon dioxide plus 2 mM nano-iron dioxide).